Mengembangkan Pelayanan Anak Berbasis Teokrasi: Menyediakan Dasar Rohani yang Kokoh dalam Masa Kini - Purbodiningrat, Movta Rahindra; Pedro, Indriyanto; Dwikoryanto, Matius I Totok (Sekolah Tinggi Teologi Kanaan Nusantara, 2024)
Children's services are keywords in shaping society's future, and spiritual and moral foundations are important components in children's character education. In the context of changing times, a